Smart antenna systems and wireless lans - Okamoto, Garret T. (Kluwer international series in engineering and computer science, 2002)
This book covers the design and mechanics of smart antenna systems and their compatibility with the worldwide wireless LAN standard (IEEE 802.11). Included are applications for Wireless LANs, terrestrial and satellite cellular systems, wireless data distribution systems, and other advanced systems. In-depth coverage is provided on utilizing smart antenna systems to increase network capacity, reduce the effects of channel fading, extend antenna battery life, and enhance the range of any wireless communications systems. The author has also included a wide range of testbed experimental results on diversity gain, LEO Iridium-like satellite emulation, as well as other advanced topics such as MAC and PHY layers, dynamic slot assignment, timing synchronization, and spatial signature properties of a smart antenna system. Many of these topics are being presented for the first time in an organized, readable book form. Smart Antenna Systems and Wireless LANs is a timely book for designers, engineers, and researchers of wireless communications systems.